Calculation of spectral weighting functions for the solar photobleaching of chromophoric dissolved organic matter in temperate lakes - Osburn, Christopher L. (2001)
The effect of solar radiation on the dissolved absorption coefficient (aCDOM[λ]), which reflects the concentration of chromophoric dissolved organic matter (CDOM), was investigated in several lakes near Bariloche, Argentina and in northeastern Pennsylvania, USA. Samples of 0.2 μm filtered lake water were exposed in quartz tubes to different portions of the solar spectrum using optical cutoff filters to remove parts of the ultraviolet (UV) region of the solar spectrum. Changes in the spectral absorption in these samples and the absorbed incident energy were used to calculate spectral weighting functions (SWFs) for the photobleaching (PB) of CDOM. PB was measured as the loss of aCDOM(λ) (the aCDOM[λ] was averaged from 280 to 500 nm) per unit absorbed energy. CDOM from humic and clear lakes, as well as from a Sphagnum bog and an algal culture, was used in the experiments covering a wide range of carbon sources. We used an iterative, nonlinear optimization method to fit the measured results to a simple exponential function in order to generate each SWF. Comparing individual SWFs calculated for various CDOM sources, we computed a summary SWF from the experiments using epilimnial CDOM from our study lakes. Our summary SWF was able to explain 80-90% of the observed variance in our exposure experiments, and we were able to predict PB results obtained for other Argentine lakes (mean error 14.5%). Finally, we calculated that the effect of UV-B radiation on PB was small (<20% of total decrease in the absorption coefficient) compared to UV-A and blue light radiation. This suggested that increased UV-B radiation due to stratospheric ozone depletion would not greatly increase the photobleaching of whole water column CDOM in Patagonian lakes (<10%).